In vivo biosynthesis of retinoic acid from beta-carotene involves and excentric cleavage pathway in ferret intestine - X Hébuterne; X D Wang; D E Smith; G Tang; R M Russell (Journal of Lipid Research, 1996)
This study was done to determine whether retinoic acid can be produced by excentric cleavage of beta-carotene in vivo. By using an inhibitor of retinaldehyde oxidation, citral, either retinaldehyde or beta-carotene was incorporated in a micellar solution and perfused through the upper portion of small intestine of ferrets. After 2 h perfusion of 1 microM retinaldehyde, retinoic acid rose in portal blood (+3.5 +/- 1.3 nmol/L) and was detected in the intestinal mucosa (30 +/- 2 pmol/g). When citral was added at 2 mM along with retinaldehyde, retinoic acid decreased in the portal blood and retinoic acid was not detected in the intestinal mucosa. With or without the presence of citral (2 mM), the perfusion of beta-carotene (10 microM) during 2 h caused a significant rise of retinoic acid in portal blood (+2.6 +/- 0.6 nmol/L and + 4.1 +/- 0.6 nmol/L, respectively) and in liver; moreover, significant amounts of retinoic acid were detected in the intestinal mucosa (19 +/- 3 pmol/g and 36 +/- pmol/g, respectively. This study demonstrates that after intestinal perfusion of beta-carotene in the ferret in vivo, a substantial amount of retinoic acid is formed via an excentric cleavage pathway.